Validation of an algorithm to identify antiretroviral-naïve status at time of entry into a large, observational cohort of HIV-infected patients. - Gandhi, Neel R; Tate, Janet P; Rodriguez-Barradas, Maria C; Rimland, David; Goetz, Matthew Bidwell; Gibert, Cynthia; Brown, Sheldon T; Mattocks, Kristin; Justice, Amy C (Pharmacoepidemiology and drug safety, 2013)
Large, observational HIV cohorts play an important role in answering questions which are difficult to study in randomized trials; however, they often lack detailed information regarding previous antiretroviral treatment (ART). Knowledge of ART treatment history is important when ascertaining the long-term impact of medications, co-morbidities, or adverse reactions on HIV outcomes.